ANALISIS BEBAN KERJA MENTAL GURU SEKOLAH DASAR MENGGUNAKAN METODE NASA-TLX STUDI KASUS DI SDN BATU TERING - Silvia Firda Utami; Ryan Suarantalla; Koko Hermanto (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2020)
The teacher is an important element in the learning process. The role and function of the teacher, namelyeducate the life of the nation's children. The demands of the main duties and functions of the teacher to educatethe nation's children become a workload for the teacher himself. Mental workload is affected by severalfactors such as internal and external factors. Internal factors, for example, excessive work demandsthen frustration will appear in carrying out their duties. When the teacher has been feeling frustrated, thenwill have an impact on decreasing teacher performance. External factors such as the outbreak of the Covid19 virus that hit the whole world, have had a very significant impact on the world of education. Teacher andstudents are required to apply new patterns to the learning system. Learning from home, isa new learning system that must be applied during the Covid-19 pandemic. Learning systemfrom home requires teachers to go the extra mile than before. It's all because of the teacheror students are not used to doing the learning system from home.